Metaphor of Life in “Reminders of Him”: A Conceptual Metaphor Study - Desak Kadek Vitri Dwi Yani; I Made Rajeg; Ni Made Ayu Widiastuti (Pusat riset dan Inovasi Nasional, 2025)
This study explores the metaphor of life in Colleen Hoover’s novel Reminders of Him, aiming to identify the types of linguistic metaphors and analyze the conceptual metaphors that underlie them. Based on Lakoff and Johnson’s conceptual metaphor theory, which classifies metaphors into structural, ontological, and orientational categories, this study highlights the role of metaphor as a cognitive tool, not merely a stylistic device. A qualitative method was employed, with data collected using AntConc software by focusing on parts of the novel containing the word “life.” The Metaphor Identification Procedure was applied to identify linguistic metaphors, which were then categorized based on the word class of the lexical units that were used metaphorically. The results of this study show four types of linguistic metaphors involving the noun “life”: nominal, verbal, adjectival, and prepositional. These forms portray life as a physical object, a process, a possessed attribute, or a container. These linguistic metaphors reflect eight conceptual metaphors, including five ontological metaphors (life is ownership, life is a container, life is an entity, life is air, life is a place) and three structural metaphors (life is a machine, life is a journey, life is a challenge). The diversity of these conceptual metaphors illustrates the rich representation of life in the novel.